Human iPS Cell-Derived Cell Aggregates Exhibited Dermal Papilla Cell Properties in in vitro Three-Dimensional Assemblage Mimicking Hair Follicle Structures - Fukuyama, Masahiro; Tsukashima, Aki; Kimishima, Momoko; Yamazaki, Yoshimi; Okano, Hideyuki; Ohyama, Manabu (Frontiers in Cell and Developmental Biology, 2021)
Current approaches for human hair follicle (HF) regeneration mostly adopt cell-autonomous tissue reassembly in a permissive murine intracorporeal environment. This, together with the limitation in human-derived trichogenic starting materials, potentially hinders the bioengineering of human hair follicle structures, especially for the drug discovery and treatment of hair loss disorders. In this study, we attempted to reproduce anatomical relationship between an epithelial main body and the dermal papilla (DP) within HF in vitro by three-dimensionally assembling columnarly moulded human keratinocytes (KCs) and the aggregates of DP cells and evaluated how HF characteristics were reproduced in the constructs. The replaceability of human induced pluripotent stem cell (hiPSC)-derived DP substitutes was assessed using the aforementioned reconstruction assay. Human DP cell aggregates were embedded into Matrigel as a cluster. Subsequently, highly condensed human KCs were cylindrically injected onto DP spheroids. After 2-week culture, the structures visually mimicking HFs were obtained. KC-DP constructs partially reproduced HF microanatomy and demonstrated differential keratin (KRT) expression pattern in HFs; KRT14 in the outermost part and KRT13, KRT17, and KRT40 respectively in the inner portion of the main body. KC-DP constructs tended to up-regulate HF-related genes, KRT25, KRT33A, KRT82, WNT5A, and LEF1. Next, DP substitutes were prepared by exposing hiPSC-derived mesenchymal cells to retinoic acid and subsequently to WNT, BMP, and FGF signal activators, followed by cell aggregation. The resultant hiPSC-derived DP substitutes (iDPs) were combined with keratinocytes in the invented assay. KC-iDP constructs morphologically resembles KC-DP constructs and analogously mimicked KRT expression pattern in HF. iDP in the constructs expressed DP-related markers, such as vimentin and versican. Intriguingly, KC-iDP constructs more intensely expressed KRT33A, KRT82, and LEF1, which were stepwisely upregulated by the addition of WNT ligand and the mixture of WNT, SHH and EDA signaling activators, supporting that iDP exhibited biological properties analogous to DP cell aggregates in the constructs in vitro. These preliminary findings suggested the possibility of regenerating DP equivalents with in vitro hair-inductive capacity using of hiPSC-derived cell composites, which potentially reduce the necessity of human tissue-derived trichogenic cell subset and eventually allow xeno-free bioengineering of human HFs.